Price and income elasticities of oil demand in Mauritius: An empirical analysis using cointegration method. (May 2020) - Raghoo, Pravesh; Surroop, Dinesh
Abstract: There are no studies that quantify the effects of price and income on the demand of fuel oil, gasoline and diesel oil in Mauritius. In line with increasing retail prices for these commodities, there is no estimation of the effect that increasing price, income and other variables like electricity and vehicle stock have on demand of petroleum products which affects effective policymaking in this area. This study uses an ARDL–ECM model to determine consumer response on petroleum demand when price and income in Mauritius changes. The study determines the income and price elasticities of demand which is a needed parameter in transportation and taxation policies. It was found that gasoline is price and income inelastic in the short–run, diesel oil is income inelastic in the long–run and fuel oil is inelastic in the short–run but becomes elastic in the long–run, other variables being not significant. The effect of rising electricity consumption on fuel oil demand was to a ratio of 1: 1.1 on average. Vehicle stock is estimated to cause unprecedented increase in gasoline demand by nearly 3.1% on average. Results are essential for transportation and energy taxation policymaking. Highlights: We estimate price and income elasticity of demand of petroleum using an ARDL–ECM. Gasoline, diesel and fuel oil exhibit different price and income elasticities. Consumers are less responsive to changes in prices of petroleum fuels in Mauritius. We explain policy implications and past failed projects of the transport sector.